THE INFLUENCE OF SOCIAL ECONOMIC LAW ON SUSTAINABLE DEVELOPMENT: AN ANALYSIS BASED ON A LITERATURE REVIEW - Loso Judijanto; Melyana R Pugu (ADISAM Publisher, 2024)
Social economic law plays an important role in promoting sustainable development by regulating economic activities to align with social and environmental goals. Through various legal instruments, social economy law can direct economic behaviour to pay more attention to social and environmental aspects, and encourage the adoption of sustainable business practices. However, the effectiveness of social economy law in promoting sustainable development depends on consistent implementation and enforcement, as well as synergy and collaboration between various stakeholders. This literature review highlights the importance of social economy law as an effective legal framework to realise inclusive, equitable and sustainable development, with balanced attention to economic, social and environmental aspects.